Intelligent Systems Design and Applications 18th International Conference on Intelligent Systems Design and Applications (ISDA 2018) held in Vellore, India, December 6-8, 2018, Volume 2 - Abraham, Ajith; Cherukuri, Aswani Kumar; Melin, Patricia; Gandhi, Niketa (Advances in Intelligent Systems and Computing, 2020)
XXI, 1114 p. 569 illus., 387 illus. in color.